The genesis of the second wave and the probable way forward for India - Aravindakshan, Rajeev; Srivastava, Siddharth (Indian Journal of Community Health, 2021)
An unprecedented pandemic affecting 210 countries emerged in the watershed year of 2020 and involved India as well (1). We mined the number of daily cases of three equal periods of importance during the evolution of the pandemic in India, namely 1) initial lockdown (March-April 2020), 2) early days of unlocking (June-July 2020), and 3) second wave (March April 2021). Notice the March 2020 series in [Figure 1] and country-wise cases in [Figure 2], and we can observe that India was able to sustain itself against the first wave of the SARS Coronavirus-2 in a much better way compared to other developed countries. Social lockdown and other preventive strategies paid off even in the face of criticisms regarding lack of preparedness and economic slowdown due to strict enforcement of harsh measures. Soon, there were demands of decentralized control measures with more testing and local containment measures than the centrally dictated regimen. Lockdown was suggested for only local clusters with high positivity rather than a general clampdown (2). The June-July series in [Figure 1] represents the increasing numbers of cases resulting from suspicions, fear-mongering, and resultant relaxation in social restrictions as part of the phase-wise unlocking across the country.